Risk factors for cutaneous reactions to allopurinol in Kinh Vietnamese: results from a case-control study - Minh Duc Do (Arthritis Research & Therapy, 2020)
Abstract Objective The aim of this study was to investigate risk factors for cutaneous adverse reactions (CARs) in Kinh Vietnamese. Methods All patients were prospectively recruited in Ho Chi Minh City. Presence of the HLA-B*58:01 allele was determined by real-time PCR-sequence-specific amplification by using the PG5801 Detection Kit (Pharmigene, Taipei). Patients with severe (SCARs) and mild (MCARs) CARs and controls were compared for differences in features prospectively collected, and odds ratios (ORs) with 95% confidence intervals (CIs) were estimated. Results On comparing 32 patients with SCARs and 395 tolerant controls, we identified eight strong risk factors: increased age (OR 15.1 [95% CI 5.8–40.1], P < 0.0001), female sex (OR 333 [40–43,453], P < 0.0001), allopurinol for asymptomatic hyperuricemia (OR 955 [120–125,847], P < 0.0001), allopurinol starting dose > 150 mg (OR 316 [101–122], P < 0.0001), diuretics intake (OR 304 [35–40,018], P < 0.0001), eGFR < 60 ml/min/1.73 m2 (OR 100 [32–353], P < 0.0001), history of allopurinol-induced skin reaction (OR 78 [6–10,808], P = 0.004), and HLA-B*58:01 carriage (OR 147 [45–746], P < 0.0001). HLA-B*58:01 allele frequency in controls was 7.3%. For MCARs (n = 74), risk factors were eGFR < 60 ml/min/1.73 m2 (OR 4.9 [1.61–14.6], P = 0.006), history of allopurinol-induced skin reaction (OR 27 [2–3777], P = 0.01), and asymptomatic hyperuricemia (OR 27 [2–3777], P = 0.01). Conclusion This study confirmed 8 risk factors, including HLA-B*58:01, for SCARs and identified 3 risk factors for MCARs in Kinh Vietnamese. HLA-B*58:01 genotyping could guide the indication for allopurinol in Kinh Vietnamese patients with gout.